2014
DOI: 10.1016/j.chom.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus VP24 Targets a Unique NLS Binding Site on Karyopherin Alpha 5 to Selectively Compete with Nuclear Import of Phosphorylated STAT1

Abstract: SUMMARY During anti-viral defense, interferon (IFN) signaling triggers nuclear transport of tyrosine phosphorylated STAT1 (PY-STAT1), which occurs via a subset of karyopherin alpha (KPNA) nuclear transporters. Many viruses, including Ebola virus, actively antagonize STAT1 signaling to counteract the antiviral effects of IFN. Ebola virus VP24 protein (eVP24) binds KPNA to inhibit PY-STAT1 nuclear transport and render cells refractory to IFNs. We describe the structure of human KPNA5 C-terminus in complex with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
256
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(274 citation statements)
references
References 44 publications
12
256
0
2
Order By: Relevance
“…This result suggests that VP24 plays a key role in the different virulence in different outbreaks according to the classification and the different lethality of each subspecies. This discovery is consistent with other medical research that VP24 is the molecular determinant of ebolavirus virulence (Xu, 2014). We suggest that VP24 should be the most important target to block when we develop drugs or vaccines.…”
Section: Ebolavirus Classification Based On Natural Vectorssupporting
confidence: 75%
See 1 more Smart Citation
“…This result suggests that VP24 plays a key role in the different virulence in different outbreaks according to the classification and the different lethality of each subspecies. This discovery is consistent with other medical research that VP24 is the molecular determinant of ebolavirus virulence (Xu, 2014). We suggest that VP24 should be the most important target to block when we develop drugs or vaccines.…”
Section: Ebolavirus Classification Based On Natural Vectorssupporting
confidence: 75%
“…It is also responsible for the NP-NP interaction and replication of the viral genome (Watanabe et al, 2006). Xu (2014) showed that VP24 binds to the karyopherin alpha nuclear transporters and blocks the nuclear accumulation of STAT1, a very important component of the immune system (Xu et al, 2014). An earlier study revealed that VP35 blocks production of interferon, a critical component for immune defense against viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Ebolavirus proteins contain a significant fraction (20%) of structurally disordered regions, and the fraction of variable positions in these regions is significantly higher (p < 0.01) than in the structurally ordered regions. The 3D structures of globular regions are mostly known (Table S2) [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] except for the N-terminal zinc-finger domain of VP30, the coiled-coil domain of VP35, and protein L. Identification and analysis of structurally characterized homologs allowed us to predict the structure of the zinc-finger domain in VP30, the overall topology of NP, and the structure and catalytic sites for the catalytic domains of protein L.…”
Section: Resultsmentioning
confidence: 99%
“…The other EBOV protein that antagonizes the innate immune response, VP24, acts by mechanisms distinct from those of VP35. VP24 interacts with karyopherin ␣ nuclear transporters to prevent translocation of STAT1 to the nucleus (29)(30)(31)(32) and also binds to heterogeneous ribonuclear protein complex C1/C2 (hnRNP C1/ C2), which normally interacts with karyopherin ␣1, and partially alters the nuclear transport of hnRNP C1/C2 (33). The interaction of VP24 with karyopherin ␣1 is completely reversed by the mutation K142A (29).…”
mentioning
confidence: 99%